PENGARUH METODE KERJA KELOMPOK TERHADAP MOTIVASI BELAJAR PADA PEMBELAJARAN AKUNTANSI SYARIAH MAHASISWA PRODI PENDIDIKAN AKUNTANSI UNIVERSITAS NEGERI MAKASSAR - Muh. Fadhil Ramadhan; M. Ridwan Tikollah; Fajriani Azis; Muhammad Azis; Sitti Hajerah Hasyim (Jurnal Genta Mulia, 2025)
The purpose of this study was to analyze the influence of group work methods on learning motivation in Islamic accounting learning for students of the Accounting Education study program at Makassar State University. A total of 72 students of the Accounting Education study program at Makassar State University were used as research samples using SPSS 25. Instrument tests and hypothesis tests are the data analysis techniques used. Validity tests and reliability tests are part of instrument tests. The t-test of the coefficient of determination, pearson product moment correlation analysis and simple linear regression analysis are hypothesis tests. Based on the results of the study, the simple linear regression equation model Y = 1.749 + 0.849X showed that the competency value of problem-based learning model skills increased by one for every student added value increased by 0.849 units. The group work method has a significant effect on learning motivation, based on the results of t-test analysis obtained 0.024 < 0.005. Analysis of the coefficient of determination resulted in an r2 value of 0.77 or 77 percent which showed that the group work method contributed 77 percent to student learning motivation.The results of the Pearson Product Moment correlation analysis showed a very strong correlation between the group work method and student learning motivation, with a Pearson correlation value of 0.878.